Implementasi Nilai-Nilai Pendidikan Multikultural Kabupaten Subang - Adam Hasyim; Aldo Muhammad Derlan (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
This study discusses the implementation of multicultural education in Subang district. The fact shows that Subang Regency currently accommodates adequate plurality and multiculturalism, besides that Subang is also an area that takes advantage of the current changing times, with the target being industrial areas and metropolitan smart cities on the Rebana triangle and also the presence of the Patimban International Port, this is the case Of course, it has a lot of good potential if it can be maximally empowered, but it is prone to conflicts and frictions that can cause divisions if it is not managed properly. Through a qualitative descriptive research method, it describes how the conditions of multicultural reality in Subang Regency and its implementation analyze the values of multicultural education in the midst of the times that have an impact on people's lives. This management can be done by implementing the values of multicultural education in an area, especially in Subang, education has an important role in guiding the social order to have attitudes and views of mutual respect, tolerance, democracy, justice and mutual understanding.